2007
DOI: 10.1111/j.1365-2893.2007.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Practical use of hepatitis C virus kinetics monitoring in the treatment of chronic hepatitis C

Abstract: Prevention of hepatitis C virus (HCV) infection complications can be achieved by antiviral therapy based on the use of a combination of pegylated interferon (IFN)-alpha and ribavirin. The steady-state kinetics of HCV infection represents the treatment target. The goal is cure, which is achieved when all infected cells have been cleared from the body. Because of their intrinsic properties, real-time polymerase chain reaction (PCR) methods are rapidly replacing other technologies for routine quantification of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…HCV RNA monitoring early in treatment may help in identifying patients with little or no chance of achieving sustained virological response as well as identifying patients with a high chance of achieving sustained virological response who may benefit for a shorter treatment programme [Chevaliez and Pawlotsky, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…HCV RNA monitoring early in treatment may help in identifying patients with little or no chance of achieving sustained virological response as well as identifying patients with a high chance of achieving sustained virological response who may benefit for a shorter treatment programme [Chevaliez and Pawlotsky, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate diagnosis of HCV infection is important due to the morbidity associated with the virus, and determining the level of viral replication is important in predicting and monitoring the effect of antiviral treatment. Although quantifying viral RNA represents the standard method for identifying active infection (5,8,13), several sensitive immunoassays that detect the viral core antigen (Ag) have now been developed as an alternative to HCV RNA testing (3,4,6,9,10,12,16). The amino acid sequence of the core Ag is largely conserved among different viral isolates (14); however, genetic variability of the virus constitutes one of the major challenges to using core Ag assays for diagnosis.…”
mentioning
confidence: 99%
“…Some retrospective studies on this subject reported variable SVR results, while a recent prospective controlled study has shown that PEG-IFN and ribavirin treatment in patients aged C65 years is less tolerated than in younger patients, and poor compliance due to side effects may be responsible for the low SVR rates observed in this patient population [10][11][12][13]. Nevertheless, pre-treatment predictors of SVR have not been clearly characterized in elderly patients with HCV undergoing antiviral therapy, and it is not known whether early ''stopping rules'' for treatment can also be effectively applied to this particular patient population [14]. This is especially important in view of the possible side effects of treatment that can be more hazardous in patients who often have a high prevalence of comorbidities.…”
Section: Introductionmentioning
confidence: 87%